True Research on Super Artificial Intelligence Computer Based Satellite Deep Tech Artificial Telepathic, Neurotechnology or Mind Controller and Wireless Direct Energy Weapon, Psychotronic Cyber Crime Technologies - Arora, Pradeep Harionm (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Wireless Remote Neural Monitoring: Bridging the Gap between Brain and Technology In the field of Neuroscience and technological advancements, the concept of Deep Tech Satellite Wireless Neural Monitoring technology has emerged as a ground breaking innovation. Which has been developed to read and understand the human brain and interact with it, which is also a wireless Direct Energy weapon. These Satellite Surveillance Criminal Operators are using this Wireless Psychotronic Neuro technology on a large scale against citizens.. Cyber criminals have started taking the help of technologies like Deep tech, satellite wireless Artificial Telepathy technology and wireless Neuro technology Bio Electro Magnetic Weapon. This is illegal deep tech satellite Neuro technology Or Mind controller technology and synthetic telepathic technology which is a psychotronic weapon and Hypnotic technology. These are deep tech satellite technologies that are used to harm and control citizens from a distance. Microwave hearing, also known as Voice to Skull [V2K]. This is Brain manipulation and Silent weapon satellite technology. This Satellite Super Artificial Intelligence [AI] Computer Or Super Computer is a Big Engineering. It is also a satellite surveillance Direct Energy weapon [Non-Contact Weapon]and Radiation weapon with which these Satellite Surveillance criminal operators carry out Physical and Cyber-attacks on citizens. Satellite Surveillance criminal operators and Cyber criminals do business worth several trillion dollars through this illegal satellite deep tech technology. This true research has been done to protect citizens from illegal deep tech satellite surveillance technology and Cyber terrorism.